Integrating Domain Expertise and Artificial Intelligence for Effective Supply Chain Management Planning Tasks: A Collaborative Approach - Lick, Jonas; Schreckenberg, Felix; Sahrhage, Philipp; Wohlers, Benedict; Klöcker, Susanne; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Artificial Intelligence, Social Computing and Wearable Technologies, Vol. 113)

Engineering und Management von System of Systems–Gestaltungskonzepte im SoS-Engineering - Günther, Matthias; Göllner, Denis; Heihoff-Schwede, Jörg; Anacker, Harald; Dumitrescu, Roman (Tag des Systems Engineering 2023)

Reifegradmodell zur Einführung von Systems Engineering–Systemdenken als Handlungsfeld - Wilke, Daria; Heitmann, Rebecca; Tekaat, Julian; Anacker, Harald; Dumitrescu, Roman (Tag des Systems Engineering 2023)

Hybrid design approach for the design of high-frequency components in MID technology - Mager, Thomas; Dumitrescu, Roman

Technology education in elementary school using the example of 'learning robots' – development and evaluation of an in-service teacher training concept - Janicki, Nicole; Tenberge, Claudia (Australasian Journal of Technology Education)
The context of the study is the increasing digitalisation of the living environment of primary school students, which is to be introduced into primary schools according to theoretical and educational policy guidelines. In this regard, further teacher training on digital media in classrooms are particularly relevant, on the one hand to promote teachers’ digital-related pedagogical knowledge and content knowledge (DPaCK). On the other hand, studies also reveal positive correlations among teacher training, teaching activities, and students’ learning outcomes. In-service teacher training courses with adaptive support by a trainer in particular have proven to be effective. Against the background of various research studies on professional development of teachers, a corresponding model of tripartite learning outcomes has been established and serves as a broad theoretical framework. However, the specific relationship between in-service teacher training with adaptive support, DPaCK, and computational thinking of primary school students in the context of the German primary school subject Sachunterricht has not been sufficiently studied. Therefore, the following research questions can be derived: (1) To what extent does training with adaptive support on the topic of learning robots contribute to the development of teachers’ DPaCK? (2) Which effects can be ascertained on the students’ computational thinking in technology-related Sachunterricht? To investigate this relationship, an intervention study in a pre-post design with an experimental group, a control group, and a baseline is appropriate. As results are not yet available at this point, the present paper focuses on the presentation of the theoretical background and empirical approaches.
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

Diaspora-Kurzgeschichten im fremdsprachlichen Unterricht Englisch: Ein neuer didaktischer Impuls? - Bauer, Maike

Diaspora-Kurzgeschichten im fremdsprachlichen Unterricht Englisch: Ein neuer didaktischer Impuls? - Bauer, Maike

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe vom 27. bis 29.09.2023 an der Universität Siegen - Janicki, Nicole

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der gemeinsamen Jahrestagung der DGTB und GATWU vom 21. bis 22.09.2023 an der Universität Potsdam - Janicki, Nicole

Standardization as a Catalyst for Extending Ressouces and Capabilities in Service Systems Engineering: Findings from the omlox case - Marx, Emanuel; Daudrich, Roman; Pauli, Tobias; Matzner, Martin; Beverungen, Daniel (Journal of Service Management Research)
(Smart) service systems have inspired the emergence of a new research area that builds on smart, connected products and networked business models with smart services and brings together various social-science and technological disciplines. However, the factors that lead to successful service systems engineering initiatives have remained under-explored, despite their increasing significance in industry. In particular, the role of standardization is unclear, even though it seems to be central to making smart products interoperable and to establishing innovative (smart) service systems. In an exploratory case study of the standardization initiative omlox, we set out to identify and investigate empirically the effects that standardization can have on engineering (smart) service systems. Our focus is to determine how standardization can assist a company in accessing external resources and capabilities for recombinant service innovation. The results reveal that compliance with a standard enables companies to tap into compatible solutions, data, and knowledge from external stakeholders and that participation in standardization initiatives can be a platform for identifying potential collaboration partners. We conclude that standardization plays a major role in all phases of service systems engineering, from analysis to design and implementation.

Modular Toolbox for Low-Code Development of Individual Augmented Reality Applications in Unity - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Open Science in Engineering)

Future-robust evolution of product portfolios: Need for action from theory and practice - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Interacting Forces for a Resilient, Future-robust Evolution of Product Portfolios - Wiederkehr, Ingrid; Schlegel, Michael; Koldewey, Christian; Rapp, Simon; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)

Guidelines for providing digital twins - Göllner, Denis; Dzienus, Sophie; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)

Mehr Innovationen durch Venture Clienting – Fallstudie zur Initiative „Stratosfare“ - Machon, Fabian; Haarmann, Lennard; Rabe, Martin; Dumitrescu, Roman; Bierbüsse, Marie; Tack, Mareen; Hanke, Rebecca; Kinder, Daniel (Vorausschau und Technologieplanung)

Bridging the Gap between Product Innovation and Product Planning: A literature-based Conceptual Investigation - Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman; Schlegel, Michael; Albers, Albert

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (Learning in the Age of Digital and Green Transition. ICL 2022. Lecture Notes in Networks and Systems)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Ontology for Future-robust Product Portfolio Evolution: A Basis for the Development of Models and Methods - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Towards a systematic approach for Prescriptive Analytics use cases in smart factories - Weller, Julian; Nico Migenda, Nico Migenda; Rui Liu, Rui Liu; Arthur Wegel, Arthur Wegel; Martin Kohlhase, Martin Kohlhase; Wolfram Schenck, Wolfram Schenck; Sebastian von Enzberg, Sebastian von Enzberg; Dumitrescu, Roman